Length and PKA Dependence of Force Generation and Loaded Shortening in Porcine Cardiac Myocytes - Kerry S. McDonald; Laurin M. Hanft; Timothy L. Domeier; Craig A. Emter (Biochemistry Research International)
In healthy hearts, ventricular ejection is determined by three myofibrillar properties; force, force development rate, and rate of loaded shortening (i.e., power). The sarcomere length and PKA dependence of these mechanical properties were measured in porcine cardiac myocytes. Permeabilized myocytes were prepared from left ventricular free walls and myocyte preparations were calcium activated to yield ~50% maximal force after which isometric force was measured at varied sarcomere lengths. Porcine myocyte preparations exhibited two populations of length-tension relationships, one being shallower than the other. Moreover, myocytes with shallow length-tension relationships displayed steeper relationships following PKA. Sarcomere length-Ktr relationships also were measured and Ktr remained nearly constant over ~2.30 μm to ~1.90 μm and then increased at lengths below 1.90 μm. Loaded-shortening and peak-normalized power output was similar at ~2.30 μm and ~1.90 μm even during activations with the same [Ca2+], implicating a myofibrillar mechanism that sustains myocyte power at lower preloads. PKA increased myocyte power and yielded greater shortening-induced cooperative deactivation in myocytes, which likely provides a myofibrillar mechanism to assist ventricular relaxation. Overall, the bimodal distribution of myocyte length-tension relationships and the PKA-mediated changes in myocyte length-tension and power are likely important modulators of Frank-Starling relationships in mammalian hearts.